Stability of Selected Phenolic Acids Under Simulated and Real Extraction Conditions from Plants - Małgorzata Olszowy-Tomczyk; Łukasz Paprotny; Dorota Wianowska (Molecules)
Currently, there is a significant demand for natural biologically active compounds. Emphasis is placed on improving the quality and safety of processed natural products, which is understandable in light of the frequently observed instability of natural compounds and their degradation, among others, to compounds of unknown biological activity. In this paper, the influence of typical conditions of currently used assisted extraction techniques on the stability of 5-O-caffeoylquinic acid and 1,3-di-O-caffeoylquinic acid during their simulated and real extraction from plants was investigated. In the experiments, extraction assisted by microwave radiation, ultrasound and pressure in procedures known as MASE, UASE and PLE techniques, respectively, was used. By comparing the amounts of native plant components, i.e., compounds present in the extract obtained, as shown, by the non-destructive SSDM technique with the amounts of these compounds estimated in extracts obtained by the above-mentioned techniques, it was proven that their content is variable. These differences are a consequence of two opposing processes, i.e., the success of the isolation process (its efficiency) and the degree of degradation/transformation of the main components. The results of the studies presented here can reduce the share of the second of the above, and consequently contribute to more effective obtaining of phenolic compounds from plants.